VD_FINDINFO HC / 2011 / 260 vom 18. Mai 2011 - VD Tribunal cantonal (2011)
LOYER, RÉSILIATION, DEMEURE DU DÉBITEUR, EXPULSION DE LOCATAIRE | 257d CO, 266a CO, 308 al. 2 CPC (CH), 405 al. 1 CPC (CH), 92 al. 1 CPC (CH)